TI_GERICHTE 90.2006.25 vom 4. November 2006 , Ricorso di un'associazione irricevibile per carenza di legittimazione attiva - TI Tribunale d'appello (2006)
Ricorso di un'associazione irricevibile per carenza di legittimazione attiva